An assessment of the environmental impacts associated with urban agriculture: a case of Gweru, Zimbabwe - Muswati, Tafadzwa (Midlands State University, 2018)
The study assessed the environmental impacts associated with urban agriculture in selected residential areas of Gweru Urban. Qualitative research methods were prominently utilised throughout the research and were complimented by quantitative methods. Questionnaires, structured interviews and direct observations were used in soliciting significant information relevant to the study objectives. Self-administration of questionnaires was done to 35 household units which were selected through a combination of convenience, random and referral sampling methods. Purposive sampling was also employed in selecting key informants (interviewees) from the Environmental Management Agency and Gweru City Council. The study accomplished that economic turmoil was a predominant factor that drove people into informally or formally securing land for agricultural purposes in Windsor Park 2 and Coolmoreen Plots. Research findings indicated that the majority of the farming practices employed by informal landholders had negative implications on the biophysical environment. The commonly noted ones included damage caused by veld fire, surface water pollution as a result of increase in phosphate levels, land degradation and acute deforestation. Although the Coolmoreen community was largely engaged in licenced agriculture, significant environmental implications were noted as a result of their activities. The most prominent challenges included soil contamination owing to the use of nitrogen based fertilisers and deforestation as a result of plot extension. Overall, land use and cover results from ArcGIS 10.5 indicated that drastic land cover changes were experienced in Windsor Park 2 due to urbanisation and agriculture development from the period of 2005 to 2016. The study concluded that an integrated urban land use approach can potentially minimise environmental degradation as a result of agro-activities. This can only be realised through the formulation and implementation of a comprehensive policy involving all the relevant stakeholders in the sector (including informal landholders). The drive to implement a suitable Gweru urban agriculture policy by the responsible bodies has to be explored since ignorance concerning the implications of agricultural activities on urban ecology can hinder sustainable development at city level.